Analisis Etika Komunikasi Guru dalam Interaksi Pembelajaran di Kelas 1 SD N 11 Palangka - Apri E.Simamora; Emya.P Br Bangun; Marsella Sinaga; Rebecca C.Siregar; M.Faisal Riza; Tomo Tomo (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to determine the communication ethics of teachers in learning interactions in grade 1 of Palangka State Elementary School 11. This study uses a descriptive qualitative method with data collection techniques in the form of interviews and observations. The resource person in this study was a grade 1 teacher of Palangka State Elementary School 11, namely Mrs. Franciska Julia. The results of the study indicate that teacher communication ethics have an important role in creating effective and comfortable learning for students. Teachers implement good communication through the use of polite language, two-way communication, providing opportunities for students to express opinions, the ability to understand student characters, and emotional control in dealing with various situations in the classroom. In addition, teachers also face several communication barriers, such as the use of language that students do not understand and the influence of digitalization developments on student behavior. In overcoming these obstacles, teachers use a patient, simple, and communicative approach so that students can understand the learning well. This study shows that teacher communication ethics greatly influences learning comfort, character formation, and student learning success in elementary schools.